An oxide solid electrolyte membrane for all-solid-state lithium battery and a preparation method thereof

The preparation process of oxide solid electrolyte membrane in all-solid-state lithium batteries is optimized through the method of aggregation and pressure-keeping, and the problems of insufficient mechanical binding force and low ionic conductivity are solved, and the high density and electrochemical performance are improved, which is suitable for commercial applications.

CN119786708APending Publication Date: 2025-04-08ZHEJIANG FUNLITHIUM NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411755181.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The oxide solid electrolytes in existing all-solid lithium batteries have problems such as insufficient mechanical binding force, low ionic conductivity and high production costs during the preparation process, which is difficult to meet the requirements of commercial applications.

Method used

The all-solid oxide solid electrolyte membrane is prepared by aggregation and pressure-keeping method. By optimizing the ratio design of coarse particles to fine particles, the fine particles can effectively fill the gaps between coarse particles, improve the density and binding force of the material, avoid the use of binders, and use cold pressing molding at room temperature.

Benefits of technology

The high density and mechanical bonding force of the oxide solid electrolyte membrane are achieved, excellent electrochemical performance is maintained, production costs are reduced, suitable for mass production, and structural stability of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166086470000071
    Figure BDA0005166086470000071
  • Figure HDA0005166086480000011
    Figure HDA0005166086480000011
  • Figure HDA0005166086480000021
    Figure HDA0005166086480000021
Patent Text Reader

Abstract

The invention discloses an oxide solid electrolyte membrane for an all-solid-state lithium battery and a preparation method thereof. The preparation method of the oxide solid electrolyte membrane for an all-solid-state lithium battery comprises the following steps: S1, under the protection of an inert atmosphere, adding LATP powder and LZSP powder into deionized water in a certain proportion, and uniformly mixing to obtain a precursor mixture; S2, drying the precursor mixture to remove the deionized water, and obtaining NASICON-type solid electrolyte particles; S3, sieving the solid electrolyte particles to obtain coarse particles and fine particles; S4, placing the coarse particles and the fine particles in a mold in a certain proportion, and cold pressing to obtain the all-solid-state oxide solid electrolyte membrane; the advantages are that the molding is performed by pressing at room temperature, the production cost is low, the ionic conductivity is high, and the oxide solid electrolyte is conducive to the commercial application of the oxide solid electrolyte in the all-solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state lithium-ion batteries, and in particular relates to an oxide solid electrolyte membrane for an all-solid-state lithium battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been widely used in consumer electronics, automobiles, and energy storage due to their high energy density, long cycle life, and stable operating voltage. However, with the increasing demand for battery safety and performance, the limitations of traditional liquid batteries in terms of safety (such as leakage, thermal runaway) and charge and discharge efficiency have gradually emerged. This limitation has prompted researchers to explore safer and more efficient battery technology, and all-solid-state lithium batteries have become a research hotspot. Compared with liquid batteries, all-solid-state lithium batteries use solid electrolytes instead of flammable liquid electrolytes, showing better safety, thermal stability, and a wider electrochemical window.

[0003] In all-solid-state lithium batteries, solid electrolytes are core materials that directly affect the ionic conductivity, cycle life, and safety performance of the battery. Currently, oxide solid electrolytes, such as NASICON-structured LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), because of its excellent chemical stability and high safety, and its ability to operate stably under high voltage conditions, has become the focus of research. Oxide solid electrolytes generally require the addition of adhesives or high-temperature sintering during the preparation process. Although the addition of adhesives can improve mechanical properties, it will significantly reduce ionic conductivity. Although high-temperature sintering can improve density and ensure ionic conductivity, the sintering process is complicated and there are many uncontrollable factors (element volatilization, thermal stress-induced cracks or pores, etc.), which makes it difficult to avoid the generation of grain boundary defects. The consistency of the produced oxide solid electrolytes cannot be guaranteed, which is ultimately not conducive to the commercial application of oxide solid electrolytes in all-solid-state lithium batteries. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an oxide solid electrolyte membrane for an all-solid-state lithium battery and a preparation method thereof, which is pressed and formed at room temperature, has a low production cost and high ionic conductivity, and is conducive to the commercial application of oxide solid electrolytes in all-solid-state lithium batteries.

[0005] The technical solution adopted by the present invention to solve the above-mentioned technical problems is: an oxide solid electrolyte membrane for an all-solid-state lithium battery, comprising a NASICON-type lithium-ion ceramic electrolyte, the chemical formula of the NASICON-type lithium-ion ceramic electrolyte being aLi2O·bAl2O3·cTiO2·dZrO2·eSiO2·fP2O5 (1.8≤a≤2.4, 0.05≤b≤0.2, 4.8≤c+d+e≤6.3, 1.4≤f≤2.5).

[0006] And a method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery, comprising the following steps:

[0007] S1. Add LATP powder and LZSP powder into deionized water in a certain proportion and mix them evenly to obtain a precursor mixture;

[0008] S2, drying the precursor mixture to remove deionized water to obtain NASICON-type solid electrolyte particles;

[0009] S3, sieving the solid electrolyte particles to obtain coarse particles and fine particles;

[0010] S4. Under the protection of an inert atmosphere, coarse particles and fine particles are placed in a mold in a certain proportion and cold pressed to obtain an all-solid oxide solid electrolyte membrane.

[0011] Preferably, in step S1, the mass ratio of LATP powder to LZSP powder is (1-5):1, and the mass ratio of powder to deionized water is (1-20):40.

[0012] Preferably, in step S1, the mixing method is stirring and mixing, the stirring speed is 300-1000 rpm, the stirring temperature is 20-100° C., and the stirring time is 1-10 h.

[0013] Preferably, in step S2, the drying temperature is 60-180° C., and the drying time is 3-24 hours.

[0014] Preferably, in step S3, the particle size of the coarse particles is 500-1000 nm, and the particle size of the fine particles is 100-1000 nm.

[0015] Preferably, in step S4, the mass ratio of coarse particles to fine particles is (1-5):1, and the particle size ratio of coarse particles to fine particles is (1-10):1.

[0016] Preferably, in step S4, the cold pressing pressure is 600-1000 MPa and the time is 30-600 s.

[0017] Preferably, in step S4, the thickness of the all-solid oxide solid electrolyte membrane is 30 to 1000 μm.

[0018] Compared with the prior art, the advantages of the present invention are:

[0019] 1. Prepare all-solid oxide solid electrolyte membrane by subpackaging and pressure maintenance, optimize the ratio design of coarse particles and fine particles, so that fine particles can effectively fill the gaps between coarse particles to improve the density of the material (reach 6.03g / cm 3 ) and bonding strength, and can effectively enhance the mechanical bonding strength between particles without the use of a binder, solving the problem of insufficient mechanical bonding strength in oxide cold pressing, thereby improving the structural stability and applicability of the material;

[0020] 2. This solution does not require the use of adhesives, significantly reducing the adverse effects on ionic conductivity, ensuring that the material maintains excellent electrochemical properties while improving mechanical properties, meeting the high performance requirements of all-solid-state batteries;

[0021] 3. Compared with the sintering process, this cold pressing preparation method does not require high-temperature treatment, which not only avoids the generation of grain boundary defects, but also reduces energy consumption and has a lower production cost. The produced all-solid oxide solid electrolyte membrane has good consistency and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The EIS curve is the EIS curve of the all-solid oxide solid electrolyte membrane of Example 1.

[0023] Figure 2 The EIS curve is the EIS curve of the all-solid oxide solid electrolyte membrane of Comparative Example 1.

[0024] Figure 3 This is the alternating current impedance diagram (EIS curve) of the all-solid oxide solid electrolyte membrane of comparative example 3. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to the embodiments.

[0026] Example

[0027] A method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery comprises the following steps:

[0028] S1. Add LATP powder and LZSP powder into deionized water in a certain proportion and mix them evenly to obtain a precursor mixture;

[0029] S2, drying the precursor mixture to remove deionized water, the drying temperature is 60 to 180° C., and the drying time is 3 to 24 hours to obtain NASICON type solid electrolyte particles;

[0030] S3, sieving the solid electrolyte particles to obtain coarse particles and fine particles;

[0031] S4. Under the protection of an inert atmosphere, coarse particles and fine particles are placed in a mold in a certain proportion, and cold pressed at a pressure of 600 to 1000 MPa and a time of 30 to 600 s to obtain an all-solid oxide solid electrolyte membrane with a thickness of 30 to 1000 μm.

[0032] The all-solid oxide solid electrolyte membrane is a NASICON type lithium ion ceramic electrolyte with a chemical formula of aLi2O·bAl2O3·cTiO2·dZrO2·eSiO2·fP2O5 (1.8≤a≤2.4, 0.05≤b≤0.2, 4.8≤c+d+e≤6.3, 1.4≤f≤2.5), and an ion conductivity greater than or equal to 0.10mS / cm.

[0033] In step S1, the mass ratio of LATP powder to LZSP powder is (1-5):1, and the mass ratio of powder to deionized water is (1-20):40; the mixing method is stirring and mixing, the stirring speed is 300-1000 rpm, the stirring temperature is 20-100° C., and the stirring time is 1-10 hours.

[0034] In step S3, the particle size of the coarse particles is 500-1000 nm, the particle size of the fine particles is 100-1000 nm, and the particle size ratio of the coarse particles to the fine particles is (1-10):1.

[0035] In step S4, the mass ratio of coarse particles to fine particles is (1-5):1, preferably (1-2):1.

[0036] Embodiment 1,

[0037] A method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery comprises the following steps:

[0038] S1. Add LATP powder and LZSP powder into deionized water in a mass ratio of 2:1, and mix them evenly under the conditions of a stirring speed of 1000 rpm, a stirring temperature of 25°C, and a stirring time of 10 h to obtain a precursor mixture, wherein the mass ratio of LATP powder and LZSP powder to deionized water is 1:2;

[0039] S2, drying the precursor mixture to remove deionized water, the drying temperature is 180°C, the drying time is 24h, and NASICON type solid electrolyte particles are obtained;

[0040] S3, sieving the solid electrolyte particles to obtain coarse particles and fine particles, the median particle size of the coarse particles is 500 nm, the median particle size of the fine particles is 500 nm, and the particle size ratio of the coarse particles to the fine particles is 1:1;

[0041] S4. Under the protection of a nitrogen atmosphere, coarse particles and fine particles are placed in a mold at a mass ratio of 2:1, and cold pressed at a pressure of 1000 MPa and a time of 600 s to obtain an all-solid oxide solid electrolyte membrane with a thickness of 100 μm.

[0042] The all-solid oxide solid electrolyte membrane is a NASICON type lithium ion ceramic electrolyte with a chemical formula of aLi2O·bAl2O3·cTiO2·dZrO2·eSiO2·fP2O5 (a=2.33, b=0.191, c+d+e=6.159, f=2.405).

[0043] Embodiment 2,

[0044] A method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery comprises the following steps:

[0045] S1. Add LATP powder and LZSP powder into deionized water at a mass ratio of 1.5:1, and mix them uniformly under the conditions of a stirring speed of 600 rpm, a stirring temperature of 60°C, and a stirring time of 5 h to obtain a precursor mixture, wherein the mass ratio of LATP powder and LZSP powder to deionized water is 1:20;

[0046] S2, drying the precursor mixture to remove deionized water, the drying temperature is 100°C, the drying time is 12h, and NASICON type solid electrolyte particles are obtained;

[0047] S3, sieving the solid electrolyte particles to obtain coarse particles and fine particles, the median particle size of the coarse particles is 800 nm, the median particle size of the fine particles is 160 nm, and the particle size ratio of the coarse particles to the fine particles is 5:1;

[0048] S4. Under the protection of a nitrogen atmosphere, coarse particles and fine particles are placed in a mold at a mass ratio of 1.5:1, and cold pressed at a pressure of 810 MPa and a time of 360 s to obtain an all-solid oxide solid electrolyte membrane with a thickness of 800 μm.

[0049] The all-solid oxide solid electrolyte membrane is a NASICON type lithium ion ceramic electrolyte with a chemical formula of aLi2O·bAl2O3·cTiO2·dZrO2·eSiO2·fP2O5 (a=2.118, b=0.143, c+d+e=5.615, f=1.93).

[0050] Embodiment 3,

[0051] A method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery comprises the following steps:

[0052] S1. Add LATP powder and LZSP powder into deionized water at a mass ratio of 5:1, and uniformly mix them under the conditions of a stirring speed of 300 rpm, a stirring temperature of 100°C, and a stirring time of 3 h to obtain a precursor mixture, wherein the mass ratio of LATP powder and LZSP powder to deionized water is 1:40;

[0053] S2, drying the precursor mixture to remove deionized water, the drying temperature is 60°C, the drying time is 3h, and NASICON type solid electrolyte particles are obtained;

[0054] S3, sieving the solid electrolyte particles to obtain coarse particles and fine particles, the median particle size of the coarse particles is 1000 nm, the median particle size of the fine particles is 100 nm, and the particle size ratio of the coarse particles to the fine particles is 10:1;

[0055] S4. Under the protection of a nitrogen atmosphere, coarse particles and fine particles are placed in a mold in a mass ratio of 1:1, and cold pressed at a pressure of 600 MPa and a time of 30 s to obtain an all-solid oxide solid electrolyte membrane with a thickness of 1000 μm.

[0056] The all-solid oxide solid electrolyte membrane is a NASICON type lithium ion ceramic electrolyte with a chemical formula of aLi2O·bAl2O3·cTiO2·dZrO2·eSiO2·fP2O5 (a=1.909, b=0.094, c+d+e=5.071, f=1.445).

[0057] Comparative Example 1

[0058] Preparation of Li with a particle size of 600 nm 1.3 Al 0.3 Ti 1.7 (PO4)3 was cold pressed for 600s under the protection of nitrogen atmosphere and at a pressure of 1000MPa to obtain an all-solid oxide solid electrolyte membrane with a thickness of 1000μm.

[0059] Comparative Example 2

[0060] In a nitrogen atmosphere, the chemical formula Li3Zr2Si2PO 12 The material preparation of (LZSP) is an amorphous-crystalline composite solid electrolyte with a thickness of 800 μm. During this process, the molding is carried out under an isostatic pressure of 700 MPa for 600 seconds.

[0061] Comparative Example 3

[0062] Preparation of Li with a particle size of 600 nm 1.3 Al 0.3 Ti 1.7 (PO4)3, and press it into sheets under a pressure of 80MPa to obtain a green sheet, and then sinter the green sheet at 900°C for 6 hours to obtain an all-solid oxide solid electrolyte membrane with a thickness of 1000μm.

[0063] The EIS curves of the all-solid oxide solid electrolyte membranes obtained in Examples 1-3 and Comparative Examples 1 and 3, and the EIS curve of the amorphous-crystalline composite solid electrolyte obtained in Comparative Example 2 were tested at 25° C. The results are shown in the following table:

[0064]

[0065] According to the test results of Examples 1-3 and Comparative Examples 1-3 and the attached Figure 1-3 It can be seen that this scheme prepares all-solid oxide solid electrolyte membrane by means of subpackaging and pressure maintenance, optimizes the ratio design of coarse particles and fine particles, and makes the fine particles effectively fill the gaps between coarse particles to improve the density of the material (reaching 6.03g / cm 3 ) and bonding strength, and can effectively enhance the mechanical bonding strength between particles without the use of a binder, solving the problem of insufficient mechanical bonding strength in oxide cold pressing, thereby improving the structural stability and applicability of the material. On this basis, the use of adhesives is avoided, significantly reducing the adverse effects on ionic conductivity, ensuring that the material maintains excellent electrochemical properties (equivalent to the all-solid oxide solid electrolyte membrane obtained by conventional sintering) while improving mechanical properties, meeting the high performance requirements of all-solid-state batteries.

[0066] Furthermore, compared with the sintering process, this cold pressing preparation method does not require high-temperature treatment, which not only avoids the generation of grain boundary defects, but also reduces energy consumption and has a lower production cost. The produced all-solid oxide solid electrolyte membrane has good consistency and is suitable for mass production.

[0067] In Comparative Example 1, although LATP itself has a certain ionic conductivity, due to the problem of poor contact between particles of a single material and excessive grain boundary resistance, its ionic conductivity is difficult to meet the application requirements of high-performance solid electrolytes.

[0068] In Comparative Example 2, although the amorphous-crystalline LZSP electrolyte film exhibits a certain room temperature ionic conductivity, its ionic conductivity is difficult to meet the application requirements of high-performance solid electrolytes.

[0069] It should be noted that the present invention has currently solved the problem of insufficient bonding force through packaging and pressure maintenance, but in the actual battery production and use in the future, it can also be further optimized in combination with other technical measures, including through structural design (such as optimizing battery diaphragm design, enhancing interface stability, etc.) to further enhance the mechanical properties of the material and ensure the long-term stability and cycle performance of the battery.

[0070] The above is an exemplary description of the present invention. Obviously, the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. An oxide solid electrolyte membrane for an all-solid-state lithium battery, characterized in that: It includes a NASICON type lithium ion ceramic electrolyte, and the chemical formula of the NASICON type lithium ion ceramic electrolyte is aLi2O·bAl2O3·cTiO2·dZrO2·eSiO2·fP2O5 (1.8≤a≤2.4, 0.05≤b≤0.2, 4.8≤c+d+e≤6.3, 1.4≤f≤2.5).

2. A method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery, characterized in that: The following steps are involved: S1. Add LATP powder and LZSP powder into deionized water in a certain proportion and mix them evenly to obtain a precursor mixture; S2, drying the precursor mixture to remove deionized water to obtain NASICON-type solid electrolyte particles; S3, sieving the solid electrolyte particles to obtain coarse particles and fine particles; S4. Under the protection of an inert atmosphere, coarse particles and fine particles are placed in a mold in a certain proportion and cold pressed to obtain an all-solid oxide solid electrolyte membrane.

3. The method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery according to claim 2, characterized in that: In the step S1, the mass ratio of LATP powder to LZSP powder is (1-5):1, and the mass ratio of powder to deionized water is (1-20):

40.

4. The method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery according to claim 2, characterized in that: In the step S1, the mixing method is stirring and mixing, the stirring speed is 300-1000 rpm, the stirring temperature is 20-100° C., and the stirring time is 1-10 hours.

5. The method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery according to claim 2, characterized in that: In step S2, the drying temperature is 60 to 180° C., and the drying time is 3 to 24 hours.

6. The method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery according to claim 2, characterized in that: In the step S3, the particle size of the coarse particles is 500-1000 nm, and the particle size of the fine particles is 100-1000 nm.

7. The method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery according to claim 2, characterized in that: In step S4, the mass ratio of the coarse particles to the fine particles is (1-5):1, and the particle size ratio of the coarse particles to the fine particles is (1-10):

1.

8. The method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery according to claim 2, characterized in that: In step S4, the cold pressing pressure is 600-1000 MPa and the time is 30-600 s.

9. The method for preparing an oxide solid electrolyte membrane for an all-solid-state lithium battery according to claim 2, characterized in that: In the step S4, the thickness of the all-solid oxide solid electrolyte membrane is 30 to 1000 μm.

Citation Information

Cited By

  • High-strength inorganic solid electrolyte membrane based on NASICON phase compounding and preparation method of high-strength inorganic solid electrolyte membrane

    CN121885739A

  • Polyformaldehyde-based composite solid electrolyte membrane and preparation method thereof

    CN122267270A